An Unmanned Aerial Vehicle Based Artificial Pollination in a Frost-affected Walnut (Juglans regia L.) Orchard - Adem Argaç; Eküle Sönmez; Dilan Ahı Koşar; Umran Ertürk (Journal of Agricultural Sciences)
The winter and spring frosts are an important problem in some walnut cultivation areas. The frost damage of catkins and female flowers results in low fruit set and yield. The temperature dropped -17.2 °C in January 2021 in the Yenişehir, Bursa, an important walnut production area in North-Western Turkey. The present study was carried out to determine the natural frost damage on catkins of some walnut cultivars and the effectiveness of an unmanned aerial vehicle (UAV) pollination, which has been developed and used in artificial pollination studies recently, on fruit set and fruit characteristics. In the experiment, two pollen concentrations (T1: 5% pollen two times; T2: 5% pollen in the first, 20% pollen in the second time) and the open pollination (control) were tested. Observations showed that frost damage on catkins varied from 57.31% (Ronde de Montignac) to 99.33% (Franquette). The initial fruit set was significantly higher in the T1 (87.74%) followed by T2 (83.89%). The final fruit set in T2 (75.16%) was higher than the T1 (74.11%), but the difference was insignificant. The box and whisker plot shows that UAV pollination treatments (T1, T2) increased the fruit set, but it was not uniform on the tree compared to open pollination. The highest nut weight, thickness, and length were obtained from control, followed by T1. The results showed that the fruit set was higher in pollination with UAV, and using less pollen (T1) was sufficient. The research results provide support for UAV treatment on supplementary pollination for walnut.